MANAJEMEN PERIOPERATIF PADA HIPERTENSI - Wiryana, Made (journal of internal medicine, 2008)
Hypertension is a leading cause of death and the most frequent preoperative abnormality in surgical patients, and becomemajor risk factor for cardiac, cerebral, renal and vascular disease during intraoperative or post-operative periode. Agressivecontrolled hypertension will decrease complications due to the damage of end organs. Consequences by taking anti-hypertensiveagents is the interaction with other medications that being used during surgery. Consideration must be taken especially due to thehalf life and adjustment dose of this medications. The National Committee 7 (JNC 7) on prevention, detection, evaluation andtreatment of high blood pressure 2003, degree of hypertension can be classified into pre-hypertension (120-139/80-89), hypertensionstage 1 (140-159/90-99 mmHg) and hypertension stage 2 (systolic pressure 160 mmHg or diastolic pressure 100 mmHg).According to the etiology, hypertension can be classified into primary hypertension (80-95%) and secondary hypertension (10-15%) due to the causes. Usually hypertension always has association with abnormality of sympathetic activity, increasing thepheripheral vascular resistance (SVR) or increasing both of them. But the most common cause of hypertension is increasing thepheripheral vascular resistance. Management perioperative of hypertension includes evaluation and optimalised patients conditionpreoperative, management patients who under influenced of anesthetic agents and treatment post operative. Patient withhypertension incline to have instability haemodinamic and more sensitive to anesthesia and surgery procedures, so carefull mustbe taken at the beginning of anesthesia and surgery until post operatively, especially to control hemodynamic. The best monitoringfor patient with hypertension is by using suitable anesthetic techniques, anesthetic agents and antihypertensive agents. Postoperative hypertension can be happened due to several factors such as, inadequate antihypertensive agents, respiratory disturbance,pain, fluid overload, or distended of the bladder. Excellent perioperative management of hypertension patients beforesurgery will decrease morbidity and mortality rate